2014
DOI: 10.1002/ijc.29264
|View full text |Cite
|
Sign up to set email alerts
|

Signal transducer and activator of transcription 5b drives malignant progression in a PDGFB‐dependent proneural glioma model by suppressing apoptosis

Abstract: Signal transducer and activator of transcription 5b (STAT5b) is likely the relevant STAT5 isoform with respect to the process of malignant progression in gliomas. STAT5b is a latent cytoplasmic protein involved in cell signaling through the modulation of growth factors, apoptosis, and angiogenesis. Previous in vitro studies have shown increased STAT5b expression in glioblastomas relative to low-grade tumors and normal brain. We recently demonstrated that phosphorylated STAT5b associates with delta epidermal gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 11 publications
(7 citation statements)
references
References 43 publications
0
7
0
Order By: Relevance
“…In fact, STAT5B can be activated by SFKs and mediate survival signalling in glioblastoma cells through direct activation of the BCL2L1 promoter [ 28 ]. Moreover, STAT5B can drive tumour progression in a PDGFB-driven glioma model and this involves increased BCL2L1 expression [ 29 ]. In the TCGA GBM patient cohort [ 4 ] STAT5B and the expression of SRC, FYN and YES are strongly correlated with the expression of BCL2L1, but also with MCL1 ( Figure 3 F and Figure S4A ).…”
Section: Resultsmentioning
confidence: 99%
“…In fact, STAT5B can be activated by SFKs and mediate survival signalling in glioblastoma cells through direct activation of the BCL2L1 promoter [ 28 ]. Moreover, STAT5B can drive tumour progression in a PDGFB-driven glioma model and this involves increased BCL2L1 expression [ 29 ]. In the TCGA GBM patient cohort [ 4 ] STAT5B and the expression of SRC, FYN and YES are strongly correlated with the expression of BCL2L1, but also with MCL1 ( Figure 3 F and Figure S4A ).…”
Section: Resultsmentioning
confidence: 99%
“…Also, crosstalk between HIF-1α and STAT3 was reported, in different tumor types, including glioblastoma [33,34]. Interest in STAT5 signaling in glioblastoma is growing, as multiple studies have shown that STAT5b drives proliferation and invasion in glioma [35,36,37,38]. This may be, in part mediated by the oncogenic EGFRvIII variant [39,40,41].…”
Section: Discussionmentioning
confidence: 99%
“…We co-expressed BIRC3 and PDGFB and independently in Ntv-a mice. Consistent with our previous studies mice were humanely euthanized by carbon dioxide asphyxiation 90 days post-injection or sooner if symptoms related to tumor burden (e.g., hydrocephalus) were present [5, 11, 36]. The brains were removed, fixed in formalin, embedded in paraffin, and sectioned for immunohistochemical analysis.…”
Section: Methodsmentioning
confidence: 99%